Change in cognitively healthy and cognitively impaired life expectancy in the United States: 2000-2010 - Eileen M. Crimmins; Yasuhiko Saito; Jung Ki Kim (Elsevier, 2016)
Objective: To determine how cognitively healthy and cognitively impaired life expectancy have changed from 2000 to 2010 among American men and women 65 years of age and over. Methods: The prevalence of dementia, cognitive impairment without dementia (CIND), and normal cognition is determined from nationally representative data from the U.S. Health and Retirement Study (HRS). Mortality rates are from U.S. Decennial Life Table for 2000 and the U.S. annual life table for 2010. Life expectancy by cognitive status is estimated using the Sullivan method. Results: Most of the increase in life expectancy has been concentrated in cognitively healthy years in this 10 year period. The increase in expected years cognitively intact at age 65, which exceeded that in total life expectancy, was 1.8 for men and 1.6 for women. Conclusion: This study provides evidence suggesting that there has been a compression of cognitive morbidity. Keywords: Cognitive life expectancy, healthy life, healthspan, dementia, CIND